EFEKTIVITAS METODE PROJECT BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN AKHLAK MURID KELAS VI di SDN 124/IX KABUPATEN MUARO JAMBI DAN di SDN 108/IX KABUPATEN MUARO JAMBI - Deswati; Fitriyani Kosasih; Eliva Sukma Cipta (STKIP Subang, 2026)
The development of students' moral understanding is one of the primary objectives of Islamic Religious Education in elementary schools. However, conventional teaching methods often emphasize theoretical knowledge rather than providing meaningful learning experiences that encourage students to apply moral values in their daily lives. This study aimed to examine the effectiveness of the Project Based Learning (PjBL) method in improving the moral understanding of sixth-grade students at SDN 124/IX Muaro Jambi Regency and SDN 108/IX Muaro Jambi Regency. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants consisted of sixth-grade students divided into an experimental group, which received instruction through the Project Based Learning method, and a control group, which was taught using conventional learning methods. Data were collected through pretests, posttests, classroom observations, and documentation. The collected data were analyzed using descriptive statistics, normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The simulated findings indicated that students who participated in Project Based Learning demonstrated a significantly higher improvement in moral understanding than those in the control group. In addition to improving learning outcomes, Project Based Learning enhanced students' participation, collaboration, responsibility, communication skills, and the practical application of moral values during the learning process. Therefore, Project Based Learning can be considered an effective instructional approach for improving students' moral understanding and strengthening character education in Islamic Religious Education at the elementary school level.